Crosstalk Minimization in VLSI Interconnects - Damanpreet Kaur; V. Sulochana (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
Crosstalk noise is often induced in long interconnects running parallel to each other .There arises a need to minimize the effect of these crosstalk noise so as to maintain the signal integrity in interconnects. So in this paper crosstalk noise is minimized using various techniques such as repeater (bidirectional buffer) insertion along with shielding, skewing and shielding & skewing simultaneously. With the help of these techniques crosstalk noise is controlled to a great extent in long interconnects. Prelayout simulations for crosstalk are carried out for different techniques at 90nm technology nodes using cadence. The influences of these techniques are analyzed and it is found that crosstalk is reduced upto 57%.